The Implementation of the Kulliyatul Muallimin Al Islamiyah (KMI) Curriculum as a Form of Acculturation of the Yemen Education System in the Curriculum of Indonesia Islamic Boarding Schools - Cahyani, Kemuning Radhita (Universitas Muhammadiyah Surakarta, 2024)
The Muadalah Islamiyah Curriculum (KMI) is an integrated curriculum designed to combine Islamic values with modern knowledge, creating graduates from Islamic Boarding Schools (pesantren) who are not only well-versed in religious studies but also equipped with the competencies needed to compete in an increasingly complex job market. This study analyzes the implementation of KMI in Indonesian pesantren, influenced by the Islamic educational traditions of Yemen. Although Yemen has a long history in Islamic education, KMI in Indonesia does not fully adopt the Yemeni educational system but rather undergoes a process of acculturation with Indonesia's social and cultural context. The findings of this study show that the implementation of KMI has significant positive impacts in several aspects, including the integration of religious knowledge and general knowledge, the improvement of educational quality, the development of social skills such as leadership and communication, and the contribution to preserving Islamic values in daily life. However, this study also identifies several challenges in implementing KMI, such as technological, economic, and human resource gaps, which can affect the quality of education in pesantren that apply KMI. Moreover, KMI strives to balance Islamic values with local culture, which poses its own challenges given Indonesia's cultural diversity. The success of KMI implementation heavily depends on the pesantren's ability to adapt to changing times and local contexts, as well as the quality of educators implementing this curriculum.